REKONSTRUKSI SISTEM PERADILAN PIDANA INDONESIA TRANSFORMASI DARI EFISIENSI PROSEDURAL MENUJU KEADILAN KEMANUSIAAN - Galih Refangga; Nurini Aprilianda; Sujiantoro Sujiantoro; Sigit Budi Santoso (Magister Ilmu Hukum, Universitas Wisnuwardhana Malang, 2026)
Reconstruction of the model of Indonesia's criminal justice system in the contemporary era faced with tensions between the efficiency of law enforcement and the protection of human rights. The birth of the new Criminal Procedure Code shows a tendency to strengthen the crime control model paradigm that is oriented towards effectiveness and efficiency, but has the potential to ignore the principle of due process of law. This study uses a normative-critical approach by examining the dynamics of regulations, judicial practices, and modern legal theories. The results of the study show that the mechanistic-legalistic judicial model has not been able to realize substantive justice because it emphasizes formal procedures too much and ignores the humanitarian dimension. Therefore, reconstruction is needed through an integrative-protection justice model that combines the family model approach, protection principles, and integrative legal theory. This model places the law not only as an instrument of enforcement, but also as a means of social recovery and the protection of human dignity. Thus, a balance between legal certainty and substantive justice can be achieved more comprehensively and sustainably. Keywords: Criminal Justice System, Substantive Justice, Due Process of Law, Crime Control Model, Protection